Resiliensi Ekonomi Syariah di Indonesia dalam Menggagas Sistem Tangguh di Masa Depan - Nur Laila Abidah; Achmad Fageh (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
In the context of globalization and increasingly complex economic challenges, the resilience of the Islamic economy is one of the most important things. The purpose of this study is to determine the resilience of the Islamic economy in Indonesia and how this system can be adopted to create economic stability in the future. The method used is a qualitative approach using descriptive analysis. The findings in the study state that government policies, sharia regulations, financial inclusion and literacy regarding Islamic finance and economics have an important role in influencing the resilience of the Islamic economy in Indonesia. In addition, technology adoption and innovation were also identified as key factors in strengthening the Islamic economic system in the future. The implication of this research is the importance of strengthening the foundation of the Islamic economy through supportive policies, clear regulations and broader Islamic economic education. This research is also expected to be able to contribute to the development of a resilient and sustainable Islamic economic system in Indonesia as well as to serve as a basis for decision-making in designing economic policies to be more inclusive for sustainability in the future.